Biometrics study of tuberculous anadara (brown shell) marketed in the market - Banchón Tanya, González; Solano Vera, Yadira (Journal of business and entrepreneurial studie, 2019)
The consumption of the brown shell in the province of Santa Elena has been increased by its excessive demand by consumers, which molluscum represents an important amount in the sustainability of the families that live from this work, despite the conversations with the lords who live from this work they tell us that it is overexploited and the destruction of the habitat which to avoid this problem that causes the reduction of the shell the MAGAP destruction in the agreement No. 149 a permanent closure and the destruction of this sea mollusk larger than 4.5 cm, for this reason there is a control of the size and weight of the shell in each port for this reason it is expected to reduce as much as possible the exploitation of these mollusks. The causes that influence which is the most important is the sustainability of the families of the province of Santa Elena that is their method of life and for reasons exceed the allowed limit of capture. The shellfish fishery is ancestral, handmade, made by women, children and men. The species Anadara tuberculosa (Sowerby 1833) and are bivalve molluscs known on the Ecuadorian coast as brown or female shell, inhabit muddy substrates (silt- clay) of mangroves. (Marco- Archivalfdpe-2011). In the Province of Santa Elena there are places where this mollusk is marketed being this the source of subsistence of the merchants in certain cases is a family business giving a sense of the importance of this source of income for the province and for those who market it